Antioxidant Activity in Pharmaceutical Biotechnology Products in The Form of Formulations and Preparations of Telang Flower Kombucha Hand Soap (Clitoria ternatea L) - Maigoda, Tonny Cortis; Hariadi, Hari; Triyono, Agus; Rezaldi, Firman; Sugiono, Sugiono; Saifullah, Ipul; Munir, Misbakhul; Kurniawan, Maskun; Rohmatulloh, Rizal; Yenny, Ratna Fitry; Pamungkas, Barolym Tri; Amin, Suseno; Judiono, Judiono (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Free radicals need to be handled and even prevented so that they are not exposed to the skin, especially the hands. One solution to preventing the exposure of free radicals to the skin of the hands is to wash your hands with herbal soap which is made from the active ingredient of telang flower kombucha. Telang flower kombucha was designed as an active ingredient in the formulation and hand washing soap preparation in this research has been proven as a pharmaceutical biotechnology product in warding off free radicals. This research was designed by making a formulation and preparation of telang flower kombucha hand washing soap at concentrations of 20%, 30% and 40% then measuring it using UV-Vis spectrophotometry. Based on statistical analysis, especially post hoc analysis of pharmaceutical biotechnology products in the form of formulations and preparations of telang flower kombucha hand washing soap at a concentration of 40%, it is significantly different from 20% and 30% as a source of antioxidants.